Requirments of Protein and Energy for Broilers During summer Season - Amrita Viswanath (Department of poultry science, College of veterinary and animal sciences, 1992)
An experiment was designed and conducted to establish the requirements of protein and energy for broilers during the summer season in the hot and humid atmosphere of Kerala. Four trials were conducted in a span of two years. In each trial the following energy – protein combinations at starter, and subsequent finisher diets were tested in a completely randomised design.